Penguatan Jaringan Kerjasama Badan Usaha Milik Desa (BUMDes) Berkah Lestari Desa Jogoroto, Kabupaten Jombang, dan Pedagang Kaki Lima (PKL): Menuju Peningkatan Pendapatan dan Ekosistem Usaha yang Berkelanjutan Sesuai Syariah - Samsuri, Ali; Muttaqin, Amrul (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Community service activities aim to strengthen the welfare of street vendors (PKL) in Jogoroto Village, Jombang Regency, through a service learning (SL) approach. This service method involves a series of trainings, discussions, and direct practice led by presenters from the Jombang Regency Cooperative Service and lecturers from IAIN Kediri, Amrul Muttaqin, and MEI. Street vendors are given knowledge and skills in business management, marketing, and finance and are guided in designing a comprehensive business plan. As a result, street vendors succeeded in increasing their confidence and knowledge, as well as designing more sustainable business strategies. This activity also strengthens cooperation between street vendors and Berkah Lestari Village-Owned Enterprises (BUMDes), providing a positive impact on improving the local business ecosystem and the economic potential of street vendors in accordance with sharia principles.